THE SYSTEM OF APPLYING STYLIZATION TECHNIQUES IN MUSICAL CULTURE AND ITS EFFECTIVENESS - J.T.Yarashev; Rizoyeva Munisa Shokirovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Stylization in modern music is a relatively young phenomenon that has been developed since the era of romanticism. Until that time, composers spoke different musical languages or dialects, based on strict compliance with the conditions of etiquette, as well as the cultural life of the era and period in which it was located, not a single musical language of this period was for composers the language of individual worldview, revealing the personality of the author. In the classical period in the era of the Middle Ages and the revival of the author's individuality and interpretation of a musical work did not exist.